Acute Inflammatory Biomarker Profiles Predict Depression Risk Following Moderate to Severe Traumatic Brain Injury. Issue 3 (May 2015) - Juengst, Shannon B.; Kumar, Raj G.; Failla, Michelle D.; Goyal, Akash; Wagner, Amy Kathleen; Bell, Jeneita M.; Taylor, Christopher A.; Breiding, Matthew J.; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Objective: To examine whether acute inflammation profiles predict posttraumatic depression (PTD) risk 6 and 12 months after traumatic brain injury. Setting: University-affiliated level 1 trauma center and community. Participants: Adults with moderate to severe traumatic brain injury (acute serum levels: n = 50; acute cerebrospinal fluid (CSF) levels: n = 41). Design: Prospective cohort study. Main Measures: Patient Health Questionnaire; inflammatory biomarkers (interleukin [IL]-1β, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, tumor necrosis factor α, soluble vascular adhesion molecule [sVCAM-1], soluble intracellular adhesion molecule [sICAM-1], soluble Fas [sFAS]). Results: Higher levels of acute CSF cytokine surface markers (sVCAM-1, sICAM-1, and sFAS) in an inflammatory biomarker risk (IBR) score were associated with a 3.920-fold increase in the odds of developing PTD at 6 months (95% confidence interval: 1.163-8.672). Having sICAM-1, sVCAM-1, or sFAS above the 75th percentile had a positive predictive value of 85.7% for PTD risk at 6 months. An IBR score including inflammatory biomarkers IL-7 and IL-8 showed a trending association with 12-month PTD risk (odds ratio = 3.166, 95% confidence interval: 0.936-10.708). Conclusion: Acute CSF IBR scores show promise for identifying individuals at risk for PTD. Further research should assess acute CSF inflammatory biomarkers' relationships to chronic inflammation as a mechanism of PTD and should explore anti-inflammatory treatments for PTD, as well as prevention and screening protocols, and link inflammatory biomarkers to symptom tracking.